VD_FINDINFO HC / 2014 / 641 vom 18. August 2014 - VD Tribunal cantonal (2014)
FRAIS JUDICIAIRES, DÉPENS, RADIATION DU RÔLE, AVOCAT D'OFFICE, CURATEUR, INDEMNITÉEN GÉNÉRAL | 105 al. 1 CPC (CH), 105 al. 2 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)